Evaluation of the Concept that Pumahuasi Veins Indicate a Potential for the Existence of Underlying Undiscovered Sedex Deposits, Northern Argentina - Sangster, Alan L. (2001)
Fil: Sangster, Alan L. Servicio Geológico Minero Argentino. Instituto de Geología y Recursos Minerales; Argentina.